ANALYSIS OF DIMENSIONAL AND CALCULATIONS STRUCTURE DESIGNED BASED ON SNI 2847-2013 - Rizki Alif Ramadhan; Anita Rahmawati; Warsito Warsito (Journal Innovation of Civil Engineering (JICE), 2021)
Floor slabs are structural components of a building that have certain dimensions to transmit dead and live loads on them to be distributed to their supports. Designing the floor slabs of a building, load data will be borne by the structure, so that the planned structure is able to bear the loads and forces that work. With careful planning, it is expected that the dimensions and reinforcement of the floor slabs are economical and safe which can avoid deflection and cracks. The building being reviewed is hospitals in Surabaya. This building consists of 9 floors with a height of up to 37 m. Planning dimensions and reinforcement in this hospital building includes two-way slabs with different size variations. The analysis was carried out using the 'envelope method' in accordance with SNI 2847: 2013 (Basics of Reinforced Concrete Planning). The results of the analysis of dimensions and reinforcement in this hospital building are: a) the dimensions / thickness of the plate on the roof plate is 125 mm, while b) the reinforcement used on this floor plate is Ø10-125 and the reinforcement for Ø10-200. Each moment analyzed is contained in the analysis results table and floor slab reinforcement drawings.